People with Special Needs in Specialized Centers, From A Culture of Marginalization to A Culture of Empowerment and Inclusion -A Field Approach for The Mentally Disabled People - Bendar , Nassima (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
The idea of ​​the research is based on the process of integrating and activating the role of children with special needs - people with mental disabilities - within their local community where the problem of the handicapped and the handicapped lies in the various social conditions and contexts that are prepared for the handicap and that put unjustified restrictions and obstacles that are not based on scientific visions in front of the participation of the "handicapped" In the activities of social life, many studies indicate that the problems of life and consensual "handicaps" are not due to injury or disability itself, but rather mainly to the way the society views them, as any attempt to deal with and/or get rid of the difficulties that a person with special needs suffers from on what is believed to be the cause of disability and the problems associated with them, as a result, people with special needs were marginalized and excluded from the course of normal life, which led to the loss or limitations of their social participation as a result of social and environmental obstacles and barriers that prevent their interaction with society, such as impartiality against disability and "the handicapped" and the tendency to stigmatization and stereotyping and bureaucracy of actions, which have the effect of excluding from social life activities, It is not implying neglecting the physiological differences, but the goal is to treat this effect without committing to the provisions of the evaluative nature, with a primary focus on aspects and societal dimensions that can be changed through the general assumptions of the social model in the interpretation of disability, in which what is known as inclusion The social and professional category of this group in addition to changing the culture of society towards people with special needs - children with mental disabilities - and disability in general.